Using food pictorial metaphor in the advertising of non-food brands: An exploratory investigation of consumer interpretation and affective response. (September 2021) - Boujena, Othman; Ulrich, Isabelle; Piris, Yolande; Chicheportiche, Laëtitia
Abstract: Using visual metaphors in ads is one of the communication techniques that brands have adopted to grab consumers' attention. The phenomenon of using food pictorial metaphors in non-food brand ads has spread in recent years, and given food's sensory nature, using this cue for a non-food brand can affect the way in which consumers interpret such ads. This research seeks to understand whether and how consumers perceive and process such a rhetorical figure. An exploratory qualitative approach is taken in two studies by using semi-structured interviews to explore consumers' reactions to different types of ads with food visual metaphors. The results reveal the predominance of congruency as a key processing mechanism of the ad at three levels: (a) between the food pictorial metaphor and the brand product category, (b) between the food visual metaphor and the brand itself, and (c) between the visual metaphor and the headline. Moreover, the food appetizing dimension, ad creativity, aesthetic appreciation of the ad, and consumers' aesthetic sensitivity are all revealed to play major roles in attitudes toward the ad.